2000
DOI: 10.1128/aem.66.12.5206-5212.2000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Infected Cell Growth State on Bacteriophage Reactivation Levels

Abstract: Reactivation of UV-C-inactivated Pseudomonas aeruginosa bacteriophages D3C3, F116, G101, and UNL-1 was quantified in host cells infected during the exponential phase, during the stationary phase, and after starvation (1 day, 1 and 5 weeks) under conditions designed to detect dark repair and photoreactivation. Our experiments revealed that while the photoreactivation capacity of stationary-phase or starved cells remained about the same as that of exponential-phase cells, in some cases their capacity to support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
(22 reference statements)
1
18
0
Order By: Relevance
“…2). It might also explain the apparent lack of dark repair in the Weinbauer et al (1997) and Wilhelm et al (1998b) (Palit et al 1983), Pseudomonas aeruginosa (Kadavy et al 2000). We also detected different levels of repair in different viruses (vp6, vp1, vp11, and vp12) that infect the same host (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…2). It might also explain the apparent lack of dark repair in the Weinbauer et al (1997) and Wilhelm et al (1998b) (Palit et al 1983), Pseudomonas aeruginosa (Kadavy et al 2000). We also detected different levels of repair in different viruses (vp6, vp1, vp11, and vp12) that infect the same host (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Based on the argument that some lethal solar damage other than dimers (UVA-induced lesions) is less effectively dark repaired than 254 nm UV damage (Harm 1980) and some wavelengths of UVA inhibit excision repair (Turner & Eisenstark 1984), our methods could overestimate the amount of excision possible. Conversely, Kadavy et al (2000) have found that starved or stationary-phase hosts (modeling bacteria in the environment) have increased dark repair, perhaps due to stress response. Their data suggest that experiments done with exponential-phase cells (like this study) would underestimate the amount of excision repair possible.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of FVIB in oligotrophic seawaters is, perhaps, not surprising because even starved bacteria are known to be infected by bacteriophages and subject to lysis (Schrader et al 1997, Kadavy et al 2000. This raises the question as to why viral infection rates are so low in the Mediterranean.…”
Section: Discussionmentioning
confidence: 74%
“…The presence of different FVIB in the 2 environments might also be due to the presence of different virus-host systems. For instance, it has been shown that UVdamaged bacteriophages can be reactivated by repair mechanisms of host cells (Weinbauer et al 1997, Kadavy et al 2000, but this process varies among host-virus systems (Schrader et al 1997, Kadavy et al 2000. Further, different microbial communities could vary in their relative repair capabilities and thus influence the propagation of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The range of activity levels within a given bacterial population might be wide or might be narrow, with similar levels of activity in all the active cells. As the activity level likely influences a number of key ecological features, such as viral infection (13,14) and flagellate grazing (9), this kind of information about specific bacterioplankton populations is essential for a more in-depth understanding of the ecology of specific phylotypes. Thus, to obtain metabolic rate estimates on a single-cell level, we quantified the halo area obtained by MICRO-CARD-FISH using image analysis.…”
mentioning
confidence: 99%